Response and Behavior of Rajungan Portunus pelagicus on the Use of Natural Bait and Artificial Bait PVa Chamois - Pratama, Arizal; Musbir, Musbir; Marimba, Andi Assir (International Journal of Environment, Agriculture and Biotechnology, 2019)
Rajungan ( Portunus pelagicus ) is one of the fisheries resources that has important economic value as an export commodity. The exploitation of rajungan is done by using traps. The success of catching using traps is influenced by several factors such as traps construction, soaking time and bait, the research method uses experimental methods. This study aims to determine the comparison of responses and behavior of rajungan to natural bait and artificial bait. Two types of bait used are sardinella fish meat ( sardinella fimbriata ) and Pva Chamois. The measured time data was collected by testing the habits and speed of 10 rajungan samples in response to bait and data analysis based on the t-test using the independent t-test at 4 phases of chemical stimulation. Selain carried out a descriptive analysis of the pattern of rajungan movements in response to the bait given, the results of the analysis showed that 3 phases of rajungan behavior, namely detection, orientation, and locomotive, did not have a significant difference, whereas in the feeding initiation phase there were significant differences. Furthermore, the movement pattern shown by the rajungan in response to natural bait is a direct movement pattern while the artificial bait is a non-direct movement pattern.